Yearbook of International Humanitarian Law 2013 - Gill, T.D (Springer, 2016)
This volume contains several articles on the topic ‘Detention in non-international armed conflict’, including the Copenhagen Process, and moreover features contributions on autonomous weapons systems, Apartheid and the second Turkel Report. It also contains an elaborate Year in Review and a special section on the high-level Boundaries of the Battlefield symposium, including a conference report and several in-depth reflections on various other aspects of the symposium. The Yearbook of International Humanitarian Law is the world's only annual publication devoted to the study of the laws governing armed conflict. It provides a truly international forum for high-quality, peer-reviewed academic articles focusing on this crucial branch of international law. Distinguished by contemporary relevance, the Yearbook of International Humanitarian Law bridges the gap between theory and practice and serves as a useful reference tool for scholars, practitioners, military personnel, civil servants, diplomats, human rights workers and students.